(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Family – a fundamental human right established at Creation. Man was created by God as a unique, whole being, in the image and likeness of God. The family was founded in Eden, this being the first school where children will study. The essence of Christian education is to restore the image of God in man. The family is a group and a basic social institution, which has certain characteristics and performs roles and functions that vary in different contexts. Family flexibility is the amount of change in family leadership, the distribution of roles and the rules of mutual relationships. The tasks, roles and functions of the family presuppose the existence of a constant qualitative and quantitative relationship between parents, children, and close adults. Family values have been integrated over time into more general social values, with the individual responding and conforming differently to these social values or norms. Values change slowly and take longer to restructure. Educational values depend on the type of family interaction, characterized by the way in which individuals interact with each other within the family group and the way they open to the outside. The values of the family, the interest, and the attention it pays to education and learning are also transmitted to the children.